New Inequalities for Means
In this paper we present new inequalities for means. If 0<a<b, A(a,b)=a+b2, G(a,b)=ab, H(a,b)=2aba+b, L(a,b)=b-ab-lna , I(a,b)=1e(b^ba^a)^1b-a , we will prove seven new theorems concerning these means. 2000 Mathematics Subject Classification. 26A48, 26D20 , number=1, journal=Sarajevo Journal of Mathematics, author=Arslanagić, Š. and Bencze, M., year=2024, month=Jun., pages=39–47